Tradisi Ijazah Hadis Musalsal bil Muṣāfaḥah di Pesantren Jami’atul Qur’an Grogol Kediri - Karima Nurul Huda; Aliifatur Roudhotul Jannah; Yenni Lailatul Rosidah; Lintang Dewi Agustin (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
This research aims to uncover the tradition of granting Ijazah (certificates of authorization) for musalsal bil musafahah Hadith practiced at Jami’atul Qur’an Islamic Boarding School. The research questions to be answered include: how is the implementation and interpretation of the tradition of Ijazah for musalsal Bil musafahah Hadith within the pesantren community, and what is the role of the local leader in the transmission and transformation of this ijazah tradition from the perspective of Peter L. Berger's social construction theory? This study utilizes a qualitative approach and applies a descriptive method. To analyze the central role of the subject or local leader (Kiai Samsul Hadi), the researcher attempts to apply Peter L. Berger and Thomas Luckmann's social construction theory.The granting of Ijazah for musalsal bil musafahah Hadith at Pesantren Jami’atul Qur’an takes place during the month of Ramadan and is directly given by the Kiai to the attending students. Initially, the transmission of the Musalsal Hadith was obtained by Kiai Samsul from prominent scholars from around the world and Indonesia, including Sheikh Yasin al-Fadani, Kiai Mahrus ‘Aly, Kiai Idris Marzuqi, and Kiai Yasin Asymuni. The basis for the Ijazah and the Hadith being transmitted is the narration that